2016
DOI: 10.1002/lary.26246
|View full text |Cite
|
Sign up to set email alerts
|

Blinded randomized controlled study of a web-based otoscopy simulator in undergraduate medical education

Abstract: 1b. Laryngoscope, 127:1306-1311, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Both learning sequences resulted in significant knowledge improvement from pre-test to post-test, and sustained knowledge on retention test. Our findings add to the growing evidence that otoscopy simulation training improves otoscopic diagnostic accuracy [ 7 , 8 , 24 , 25 ]. We also found that the mobile otoscopy simulator was well-received by participants.…”
Section: Discussionsupporting
confidence: 72%
“…Both learning sequences resulted in significant knowledge improvement from pre-test to post-test, and sustained knowledge on retention test. Our findings add to the growing evidence that otoscopy simulation training improves otoscopic diagnostic accuracy [ 7 , 8 , 24 , 25 ]. We also found that the mobile otoscopy simulator was well-received by participants.…”
Section: Discussionsupporting
confidence: 72%
“…Diagnostic accuracy was low overall, with a mean score of 54%. This is similar to other studies of medical student otoscopic diagnostic scores (22.1%-61.5%), 10,16,17 as well as some studies of primary care residents and practitioners. 3,18 In our study, students were best at diagnosing ear tubes and perforations, but struggled with the other more subtle diagnoses, especially eardrum retractions.…”
Section: Discussionsupporting
confidence: 91%
“…16 Similarly, Stepniak et al found that medical students who had access to an otoscopic simulator were more accurate at diagnosing pathology in otoscopic videos compared to peers who did not have access. 17 In recent years, otolaryngology residency programs have recognized the potential benefits of using simulators to train, with Deutsch et al reporting that 78.6% of respondents had some form of onsite simulator for their training program, and 83.8% wished to participate in trials focusing on simulation intitiatives. 19 Continued developments in technology that provide improved otoscopic visualization and automated feedback may provide better ways both to enhance clinicians' otoscopic diagnostic performance and assist trainees in refining their otoscopic skills.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the students' examination skills and diagnostic ability showed improvement using web-based learning compared to revising printed lecture notes [6]. In another study in 2016 by Stepniak et al, web-based learning was found to be effective in teaching otoscopy for undergraduate medical students [8]. However, this study utilised a high end, and expensive simulator with a very limited follow-up period of only one week.…”
Section: Discussionmentioning
confidence: 93%